PERSPEKTIF MASYARAKAT KOTA MAKASSAR TERHADAP KEBIASAAN BEROLAHRAGA - Muhammad Naufal Ramadhansyah; Asri Awal; Hasyim Hasyim (Bajang Institute, 2026)
This study used a quantitative approach with a descriptive approach, aiming to describe community perspectives on exercise habits in Makassar. The population in this study was the entire population of Makassar City, while the sample size was 150 respondents, determined using purposive sampling techniques based on certain criteria, such as being of productive age and residing in Makassar. The research instrument used was a questionnaire with a five-level Likert scale, compiled based on indicators of perception, habits, motivation, access to facilities, and social support. Data collection was carried out by distributing questionnaires in person and online to respondents who met the research criteria. The collected data were then analyzed using descriptive statistical analysis techniques. Based on the results of this study regarding the perspectives of Makassar City residents on exercise habits, it can be concluded that, in general, the community has a positive perception of the importance of exercise, especially in maintaining health and fitness, and preventing disease.